The Impact of Online Learning on Undergraduate English Students’ Achievement - Erizar , Erizar; Yulia, Astri; Marzuki , Abdul Gafur; Hidayati, Tuti; Juliana, Rena (Journal of English Education and Teaching, 2024)
Blended learning, integrating traditional face-to-face instruction with online components, has gained momentum in higher education. This study aimed to explore the effect of blended learning on the academic performance of students enrolled in the English Department across multiple universities in Aceh, Indonesia. The research specifically aims to compare the effectiveness of blended and offline learning models in facilitating students' learning achievements. The study population encompasses undergraduate students from seven distinguished universities within the Aceh Province, making the research findings relevant and applicable to a diverse range of educational institutions. Quantitative data, gathered through a survey method, formed the basis of this research, enabling a thorough analysis of students' learning outcomes in both blended and offline learning environments. The results of the study reveal a compelling insight: there is no statistically significant difference in students' learning achievements between blended and offline learning models (P = 0.062 > 0.05). This intriguing finding challenges traditional perceptions and underscores the potential of blended education as a viable and effective alternative to conventional classroom learning within the English Department curriculum. The implications of these results are far-reaching, suggesting that universities and lecturers can leverage blended learning platforms without compromising the quality of education provided to English Department students. This research contributes valuable insights to the ongoing discourse on the evolution of educational methodologies, emphasizing the importance of embracing technology-enhanced learning approaches. As the world continues to advance digitally, this study provides a foundation for future exploration and implementation of blended learning strategies, fostering an inclusive and innovative educational landscape for students in Aceh, Indonesia.